Income Effect on Labor Outcomes for People Living in Poverty: the case of PROGRESA - Mesén Vargas, Juliana (2021)
This paper studies the income effect of cash transfers on adult labor outcomes. I use data of PROGRESA, a large cash transfer program in Mexico that provides money to households subject to the condition that school aged kids go to school. I focus on a subsample of the eligibles for whom the conditionality is not a constraint. This allows me to shut-down the substitution effect that the conditionality of the transfer may induce. In practice, it is as if PROGRESA was an unconditional cash transfer for this subpopulation. Contrary to standard beliefs, I find that the income effect on labor outcomes is not negative.